2016
DOI: 10.1038/srep23488
|View full text |Cite|
|
Sign up to set email alerts
|

Precipitation shapes communities of arbuscular mycorrhizal fungi in Tibetan alpine steppe

Abstract: Tibetan Plateau is one of the largest and most unique habitats for organisms including arbuscular mycorrhizal fungi (AMF). However, it remains unclear how AMF communities respond to key environmental changes in this harsh environment. To test if precipitation could be a driving force in shaping AMF community structures at regional scale, we examined AMF communities associated with dominant plant species along a precipitation gradient in Tibetan alpine steppe. Rhizosphere soils were collected from five sites wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
34
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 54 publications
9
34
0
2
Order By: Relevance
“…The distinct AM fungal community compositions were also found along altitudinal gradients on the basis of analysis of spore morphology6 and molecular techniques847. Furthermore, we found that the AM fungal community composition was significantly related to soil moisture and plant functional group composition, and was marginally related to soil TOC and available N. Indeed, these plant and soil variables showed substantial difference amongst different original elevations in this study (Supplementary Table S1), which may result in changes in AM fungal composition, as previous studies reported that AM fungal community composition was structured by plant community112449 and soil variables1314152750. Nevertheless, we found that the AM fungal community composition was not significantly influenced by the downward or upward translocation.…”
Section: Discussionsupporting
confidence: 54%
“…The distinct AM fungal community compositions were also found along altitudinal gradients on the basis of analysis of spore morphology6 and molecular techniques847. Furthermore, we found that the AM fungal community composition was significantly related to soil moisture and plant functional group composition, and was marginally related to soil TOC and available N. Indeed, these plant and soil variables showed substantial difference amongst different original elevations in this study (Supplementary Table S1), which may result in changes in AM fungal composition, as previous studies reported that AM fungal community composition was structured by plant community112449 and soil variables1314152750. Nevertheless, we found that the AM fungal community composition was not significantly influenced by the downward or upward translocation.…”
Section: Discussionsupporting
confidence: 54%
“…It has been reported that the soil fungal community composition changes under drought resulting in a decreased α-diversity (Hawkes et al, 2011;Cregger et al, 2012;Seema B. Sharma & Thivakaran A. Gobi, 2016;Zhang et al, 2016). As far as we know, the consequence of drought on the root associated fungal microbiota has not been investigated before under field conditions.…”
Section: Drought Affects the Endophytic Fungal Microbiotamentioning
confidence: 97%
“…Roots were cut into 1-2 cm length segments and washed carefully with distilled water. The root segments were bleached by 10% KOH solution with a few drops of H 2 O 2 and water-bath heating at 90 • C for 2 h, acidified with 1% HCl for 15 min, and stained in Trypan blue (0.05% in 5:1:1 lactic acid/glycerol/distilled water) at 90 • C for 15 min using the method described by Zhang et al [64]. Stained roots were then rinsed and decolorized by soaking in clean water overnight.…”
Section: Mycorrhizal Colonization Measurementmentioning
confidence: 99%
“…The Glomeromycotina sequences were resampled to eliminate the effects of different read numbers. Afterward, to further confirm the remaining OTUs belonging to AM fungi, a phylogenetic tree was constructed in MEGA v7 (Kumar, Stecher, Li, Knyaz, and Tamura 2018) using the Kimura 2 parameter model with 1000 replicates, according to the representative sequences and reference sequences of Glomeromycotina downloaded from GenBank and MaarjAM [64]. Similar OTUs were merged and renumbered to produce a final OTU table for subsequent ecological analysis.…”
Section: Sequence Data Processingmentioning
confidence: 99%